2019
DOI: 10.1016/j.drugalcdep.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and consequences in adolescents in 68 low and middle-income countries – a multi-country comparison of risks by sex

Abstract: GCK, Alcohol consumption and consequences in adolescents in 68 low and middle-income countries -a multi-country comparison of risks by sex, Drug and Alcohol Dependence (2019),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
(45 reference statements)
1
8
0
3
Order By: Relevance
“…These findings align with previous studies which have found the gender of the students to be significantly associated with substance use (Aklog et al , 2013; Makanjuola et al , 2007; Meressa et al , 2009). Earlier studies have also documented that alcohol use among males is more socially acceptable than for females (Chaiyasong et al , 2018; Leung et al , 2019).…”
Section: Discussionmentioning
confidence: 96%
“…These findings align with previous studies which have found the gender of the students to be significantly associated with substance use (Aklog et al , 2013; Makanjuola et al , 2007; Meressa et al , 2009). Earlier studies have also documented that alcohol use among males is more socially acceptable than for females (Chaiyasong et al , 2018; Leung et al , 2019).…”
Section: Discussionmentioning
confidence: 96%
“…A maioria dos estudos, a partir do ano de 2014, relatou que indivíduos entre 60 e 64 anos e 65 anos ou mais exibiam um maior consumo atual de bebidas alcoólicas, relacionando-se também ao indivíduo do sexo masculino 15 .…”
Section: Discussionunclassified
“…GSHS data from 68 low-and middle-income countries (LMICs) has showed that alcohol use in the past month among 12-15 years old ranged from 0.4% of girls in Tajikistan to 59.7% of boys in the Seychelles. 21 HBSC data has showed a declining trend for weekly intake by 15-years old in most countries in Europe between 2002 and 2014. 22 The earliest recall possible for age of initiation in these surveys was '7 years old or younger' in the GSHS and '11 years old or less' in the HSBC, but we have been unable to identify reports of 'early onset' that include a lower cut-off than 10-11 years (GSHS) or 13 years (HSBC).…”
Section: Alcohol Use By Adolescentsmentioning
confidence: 99%
“…Patterns of adolescent alcohol use vary across the globe. GSHS data from 68 low- and middle-income countries (LMICs) has showed that alcohol use in the past month among 12–15 years old ranged from 0.4% of girls in Tajikistan to 59.7% of boys in the Seychelles 21. HBSC data has showed a declining trend for weekly intake by 15-years old in most countries in Europe between 2002 and 2014 22.…”
Section: The Epidemiology Of Childhood Alcohol Usementioning
confidence: 99%